2021
DOI: 10.5796/electrochemistry.20-65159
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Dissolution of Mesoporous Layer during Metal-Particle-Assisted Etching of n-Type Silicon

Abstract: Metal-assisted etching has attracted increasing attention as a method to produce porous silicon (Si). We previously found that gold (Au)-and platinum (Pt)-particle-assisted etching causes general corrosion of the Si substrate, but not in the case of silver (Ag)-particle-assisted etching [A. Matsumoto, et al., RSC Adv., 10, 253 (2020)]. In this work, we discussed the 2 mechanism of the general corrosion with electrochemical approaches. We demonstrated that potentials of the Au-and Pt-deposited Si during the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Previously, we studied the metal-assisted etching using Pt particles as the catalysts and measured the potential of Si during etching. 21,22,48 For example, the potentials of Pt-particle-deposited n-Si and p-Si were −0.25 V 48 and 0.07 V 21 vs Ag/AgCl, respectively. The potentials of Pt-filmdeposited n-Si (after the potential drop) and p-Si are similar to that of Pt-particle-deposited n-Si and p-Si, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we studied the metal-assisted etching using Pt particles as the catalysts and measured the potential of Si during etching. 21,22,48 For example, the potentials of Pt-particle-deposited n-Si and p-Si were −0.25 V 48 and 0.07 V 21 vs Ag/AgCl, respectively. The potentials of Pt-filmdeposited n-Si (after the potential drop) and p-Si are similar to that of Pt-particle-deposited n-Si and p-Si, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…An electrochemical cell used for this study was illustrated in the previous paper. 48 As a working electrode, the Pt-deposited Si or bare Si was used. A rubber packing was inserted between the cell and Si.…”
Section: Methodsmentioning
confidence: 99%
“…An electrochemical cell was illustrated in the previous paper. 31 As a working electrode, the Ptdeposited Si or bare Si was used. A rubber packing was inserted between the cell and Si.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that the general corrosion occurs due to the dissolution of mesoporous layer by reproducing the mesoporous layer formed during the Pt-particleassisted etching by photoelectrochemical etching of bare Si and immersing it in the etching solution. 31 Mesoporous layer formation during the metal-assisted etching has been discussed from various points of view. 7,11,[14][15][16][27][28][29][30][31][32][33] As an innovative approach, Torralba et al 29 utilized a device simulator to calculate the band bending in Si during the Pt-particle-assisted etching, aiming at the control of cone-shaped pores.…”
mentioning
confidence: 99%
See 1 more Smart Citation